Membrane electrode assembly and fuel cell

By increasing the content of fibrous conductive members in the gas diffusion layer in the membrane electrode joint of the fuel cell, the problem of insufficient adhesion and drainage between the catalyst layer and the gas diffusion layer is solved, and the power generation performance and reaction of the fuel cell are improved efficiency.

CN113646934BActive Publication Date: 2024-12-17PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080025118.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-05
Publication Date
2024-12-17
Estimated Expiration
2040-03-05

AI Technical Summary

Technical Problem

The adhesion and drainage properties of the gas diffusion layer and the catalyst layer of the existing fuel cells are insufficient, which limits the high power generation performance of the fuel cells.

Method used

A membrane electrode joint structure is adopted, wherein the catalyst layer includes catalyst particles and a first conductive material, the gas diffusion layer includes a second conductive material, and the mass content of the fibrous conductive member in the second conductive material is greater than the first conductive property The content of fibrous conductive member in the material, and the gas diffusion and water discharge efficiency are improved through this structure.

Benefits of technology

The power generation performance of the fuel cell is improved, the blockage of the gas diffusion path is suppressed, and the reaction efficiency is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113646934B_ABST
    Figure CN113646934B_ABST
Patent Text Reader

Abstract

The membrane electrode assembly comprises: an electrolyte membrane; a pair of catalyst layers (120A, 120B) respectively stacked on one surface and the other surface of the electrolyte membrane; and a pair of gas diffusion layers (130A, 130B), which are respectively stacked on the surface of one of the pair of catalyst layers opposite to the electrolyte membrane and the surface of the other of the pair of catalyst layers opposite to the electrolyte membrane. One of the pair of catalyst layers includes catalyst particles and a first conductive material. The gas diffusion layer in contact with one of the pair of gas diffusion layers includes a second conductive material. The first conductive material includes a first particle-shaped conductive member and a first fibrous conductive member, and the second conductive material includes at least a second fibrous conductive member. The mass-based content K2 of the second fibrous conductive member in the second conductive material is greater than the mass-based content K1 of the first fibrous conductive member in the first conductive material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a membrane electrode assembly and a fuel cell. Background Art

[0002] The fuel cell includes, for example, a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. The pair of electrodes each includes a catalyst layer and a gas diffusion layer in this order from the electrolyte membrane side.

[0003] Patent Document 1 discloses a gas diffusion layer comprising a fluororesin, boron-modified carbon, and fibrous carbon, wherein the fibrous carbon is contained in an amount of 5 to 50 parts by weight based on 100 parts by weight of the boron-modified carbon.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-141783 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In recent years, the application fields of fuel cells have been expanding, and at the same time, fuel cells with high performance are being sought.

[0009] However, in the above-mentioned gas diffusion layer configuration, it cannot be said that the adhesion with the catalyst layer and the water-repellency are sufficient, and there is a limit to achieving a fuel cell having high power generation performance.

[0010] Means for solving problems

[0011] One aspect of the present invention relates to a membrane electrode assembly of a fuel cell, which comprises an electrolyte membrane; a pair of catalyst layers, which are respectively stacked on one surface and the other surface of the above-mentioned electrolyte membrane; and a pair of gas diffusion layers, which are respectively stacked on the surface of one catalyst layer in the above-mentioned pair of catalyst layers opposite to the above-mentioned electrolyte membrane and the surface of the other catalyst layer in the above-mentioned pair of catalyst layers opposite to the above-mentioned electrolyte membrane, wherein one catalyst layer in the above-mentioned pair of catalyst layers contains catalyst particles A and a first conductive material, and among the above-mentioned pair of gas diffusion layers, the gas diffusion layer in contact with the above-mentioned one catalyst layer contains a second conductive material, the above-mentioned first conductive material contains a first particulate conductive component and a first fibrous conductive component, the above-mentioned second conductive material contains at least the second fibrous conductive component among the second particulate conductive component and the second fibrous conductive component, and the mass-based content K2 of the above-mentioned second fibrous conductive component in the above-mentioned second conductive material is greater than the mass-based content K1 of the above-mentioned first fibrous conductive component in the above-mentioned first conductive material.

[0012] Another aspect of the present invention relates to a fuel cell including the membrane electrode assembly described above.

[0013] Effects of the Invention

[0014] According to the present invention, the power generation performance of a fuel cell can be improved.

[0015] The novel features of the present invention, which relate to both structure and content, are described in the attached technical solutions, and together with other objects and features of the present invention, can be better understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a cross-sectional view schematically showing the structure of a single cell unit of a fuel cell according to an embodiment of the present invention.

[0017] Figure 2 This is a diagram schematically showing the interior of a first catalyst layer and a first gas diffusion layer constituting a part of a membrane electrode assembly. DETAILED DESCRIPTION

[0018] A fuel cell according to an embodiment of the present invention has a membrane electrode assembly (hereinafter also referred to as "MEA"), which includes an electrolyte membrane; a pair of catalyst layers, which are stacked on one surface and the other surface of the electrolyte membrane; and a pair of gas diffusion layers, which are stacked on the surface of one catalyst layer of the pair of catalyst layers opposite to the electrolyte membrane and the surface of the other catalyst layer of the pair of catalyst layers opposite to the electrolyte membrane. One of the pair of catalyst layers is a cathode catalyst layer provided at the cathode, and the other is an anode catalyst layer provided at the anode. Hereinafter, among the pair of gas diffusion layers, the gas diffusion layer stacked on the anode catalyst layer is referred to as an "anode-side gas diffusion layer", and the gas diffusion layer stacked on the cathode catalyst layer is referred to as a "cathode-side gas diffusion layer".

[0019] The fuel cell may also include, for example, a conductive cathode spacer in contact with the cathode-side gas diffusion layer and a conductive anode spacer in contact with the anode-side gas diffusion layer. The MEA and a pair of spacers may constitute a battery cell. By stacking a plurality of battery cells in such a manner that the cathode spacer and the anode spacer are adjacent, a stack in which the battery cells are connected in series can be formed.

[0020] One catalyst layer in a pair of catalyst layers includes catalyst particles A and a first conductive material. In a pair of gas diffusion layers, the gas diffusion layer in contact with the above-mentioned one catalyst layer includes a second conductive material. The first conductive material includes a first particle-shaped conductive member and a first fiber-shaped conductive member. The second conductive material includes at least a second fiber-shaped conductive member. The second conductive material may further include a second particle-shaped conductive member. The first conductive material and the second conductive material are configured to satisfy the following condition 1.

[0021] (Condition 1)

[0022] A content K2 of the second fibrous conductive members in the second conductive material based on mass is greater than a content K1 of the first fibrous conductive members in the first conductive material based on mass.

[0023] In the present embodiment, the catalyst layer and the gas diffusion layer in contact with each other may both include a particle-shaped conductive member and a fibrous conductive member as conductive materials. However, regarding the conductive material (second conductive material) contained in the gas diffusion layer, it is also possible not to include a particle-shaped conductive member (second particle-shaped conductive member), but only to be composed of a fibrous conductive member (second fibrous conductive member). Condition 1 means that in at least one of the anode or cathode, in the catalyst layer and the gas diffusion layer in contact with each other, the content K2 of the mass basis of the second fibrous conductive member contained in the gas diffusion layer in the second conductive material is greater than the content K1 of the mass basis of the first fibrous conductive member contained in the catalyst layer in the first conductive material. Thus, gas diffusibility can be improved. In addition, water generated in the catalyst layer or attached to the catalyst layer is easily discharged to the outside via the gas diffusion layer, which can inhibit the gas diffusion path from being blocked by water (i.e., overflow).

[0024] The first fibrous conductive member and the second fibrous conductive member may both be made of the same material, or may contain the same material in at least a portion. Here, the first fibrous conductive member and the second fibrous conductive member being made of the same material means that the material is obtained from a raw material with substantially the same material as the main component and through substantially the same manufacturing process. For example, when the first fibrous conductive member includes vapor-grown carbon fibers, it means that the second fibrous conductive member also includes vapor-grown carbon fibers, or when the first fibrous conductive member includes carbon nanotubes, it means that the second fibrous conductive member also includes carbon nanotubes. At this time, the first fibrous conductive member and the second fibrous conductive member have many common or similar physical properties. Therefore, by making the physical properties of the fibrous conductive members contained in the catalyst layer and the gas diffusion layer that are in contact with each other similar, the discharge efficiency of water can be further improved.

[0025] However, even if the manufacturing process is substantially the same, the first fibrous conductive member and the second fibrous conductive member may have some differences in their composition due to, for example, impurities contained in the raw materials, or differences in subtle conditions in the manufacturing process such as processing temperature or processing time. For example, impurities contained in the fibrous conductive member, fiber diameter and fiber length of the fibrous conductive member, and fiber morphology (straight or bent) may differ between the first fibrous conductive member and the second fibrous conductive member. In this case, the first fibrous conductive member and the second fibrous conductive member can also be said to be made of the same type of material.

[0026] From the perspective of making the physical properties of the fibrous conductive members similar and improving the water discharge efficiency, whether the first fibrous conductive member and the second fibrous conductive member are made of the same material, the ratio of the fiber length of the second fibrous conductive member to the fiber length of the first fibrous conductive member can be in the range of 0.5 to 2.0. Here, the fiber length refers to the average fiber length defined later. The ratio corresponding to the above fiber length can be in the range of 0.95 to 1.05.

[0027] From the perspective of making the physical properties of the fibrous conductive members similar and improving the water discharge efficiency, whether the first fibrous conductive member and the second fibrous conductive member are made of the same material, the ratio of the fiber diameter of the second fibrous conductive member to the fiber diameter of the first fibrous conductive member can be in the range of 0.5 to 2.0. Here, the fiber diameter refers to the average fiber diameter defined later. The ratio corresponding to the above fiber diameters can be in the range of 0.95 to 1.05.

[0028] The content K2 of the second fibrous conductive member in the second conductive material is, for example, 60% by mass or more. K2 may be 70% by mass or more or 80% by mass or more. In contrast, the content K1 of the first fibrous conductive member in the first conductive material is, for example, 20 to 50% by mass, which is sufficiently smaller than K2.

[0029] The upper limit K2 of the content of the second fibrous conductive member in the second conductive material is not limited, but is 100% by mass or less, and may be 90% by mass or less.

[0030] The content K2 of the second fibrous conductive members in the second conductive material may be, for example, 60% by mass to 90% by mass.

[0031] One catalyst layer may constitute the cathode of the fuel cell. That is, the catalyst layer and the gas diffusion layer satisfying the above condition 1 may be the cathode catalyst layer and the cathode-side gas diffusion layer.

[0032] In a fuel cell using a proton-conductive polymer electrolyte membrane as an electrolyte membrane, water vapor is usually added to the fuel gas or oxidizing gas to humidify it and then supplied to the catalyst layer in order to improve the proton conductivity of the electrolyte membrane. However, part of the water vapor condenses, and the water adheres to the catalyst layer and the gas diffusion layer, sometimes blocking the gas diffusion path. In addition, when the fuel cell generates electricity, water is generated at the cathode, so the gas diffusion path is more easily blocked by water on the cathode side than on the anode side, and the necessity of discharging water is high.

[0033] By making the cathode catalyst layer and the cathode side gas diffusion layer satisfy the above condition 1, water can be discharged more effectively. In addition, the generated water is prevented from clogging the gas diffusion path, and the gas required for the reaction is easily diffused to the catalyst. As a result, the reaction efficiency is improved, and the performance of the fuel cell is easily improved.

[0034] In addition to the cathode catalyst layer, the anode catalyst layer may also include a particle-shaped conductive member and a fibrous conductive member as a conductive material. In this case, the other catalyst layer of the pair of catalyst layers contains catalyst particles B and a third conductive material. The third conductive material includes a third particle-shaped conductive member and a third fibrous conductive member.

[0035] When the anode catalyst layer includes the third fibrous conductive member, the mass-based content K3 of the third fibrous conductive member in the third conductive material may be the same as the content K1 of the first fibrous conductive member in the cathode catalyst layer. For example, the ratio K3 / K1 of the content K3 to the content K1 may be in the range of 0.5≤K3 / K1≤2.0, or in the range of 0.9≤K3 / K1≤1.1.

[0036] When the anode catalyst layer includes the third fibrous conductive member, the content K2 of the second fibrous conductive member in the cathode side gas diffusion layer may be greater than the content K3 of the third fibrous conductive member in the third conductive material based on the mass. By making the content of the fibrous conductive member contained in the cathode side gas diffusion layer greater than the content of the fibrous conductive member contained in the anode catalyst layer, it is possible to suppress the excessive back diffusion of the generated water generated in the cathode catalyst layer to the anode catalyst layer side. Thus, the diffusion of the generated water to the cathode side gas diffusion layer and the back diffusion to the anode catalyst layer side can be appropriately controlled, and the drying of the cathode catalyst layer can be suppressed.

[0037] The anode side gas diffusion layer can use the known gas diffusion layer structure, for example, carbon cloth or carbon paper can be used. The anode side gas diffusion layer may contain a conductive material (fourth conductive material), may contain a fibrous conductive member (fourth fibrous conductive member), or may not contain it. As described above, on the anode side, high drainage is not required as on the cathode side. In contrast, on the anode side, high proton diffusivity is required. At this point, even in the case where the fourth conductive material contains a fourth fibrous conductive member, the mass basis content K4 of the fourth fibrous conductive member in the fourth conductive material may be less than the above-mentioned content K2 of the second fibrous conductive member in the cathode side gas diffusion layer.

[0038] However, from the perspective of improving gas diffusivity on the anode side and improving drainage under high humidity operating conditions, the content of fibrous conductive components in the anode gas diffusion layer can also be increased so that the anode catalyst layer and the anode side gas diffusion layer meet the above condition 1.

[0039] Both the combination of the cathode catalyst layer and the cathode-side gas diffusion layer and the combination of the anode catalyst layer and the anode-side gas diffusion layer may satisfy the above-mentioned condition 1. That is, the gas diffusion layer in contact with the other catalyst layer may include a fourth conductive material, the fourth conductive material includes at least a fourth fibrous conductive member among a fourth particulate conductive member and a fourth fibrous conductive member, and the mass-based content of the fourth fibrous conductive member in the fourth conductive material is greater than the mass-based content of the third fibrous conductive member in the third conductive material.

[0040] Below, refer to Figure 1 An example of the structure of the fuel cell according to the present embodiment will be described. Figure 1 1 is a cross-sectional view schematically showing the structure of a single cell unit configured in a fuel cell according to one embodiment. Generally, a plurality of single cell units are stacked and configured in a fuel cell as a cell stack. Figure 1 , for convenience, a single battery unit is shown.

[0041] The single cell unit 200 includes a membrane electrode assembly 100, which includes an electrolyte membrane 110, a first catalyst layer 120A and a second catalyst layer 120B arranged to sandwich the electrolyte membrane 110, and a first gas diffusion layer 130A and a second gas diffusion layer 130B arranged to sandwich the electrolyte membrane 110 via the first catalyst layer 120A and the second catalyst layer 120B. In addition, the single cell unit 200 includes a first separator 240A and a second separator 240B sandwiching the membrane electrode assembly 100. One of the first catalyst layer 120A and the second catalyst layer 120B functions as an anode, and the other functions as a cathode. The electrolyte membrane 110 is larger than the first catalyst layer 120A and the second catalyst layer 120B, so the peripheral edge of the electrolyte membrane 110 is exposed from the first catalyst layer 120A and the second catalyst layer 120B. The peripheral edge of the electrolyte membrane 110 is sandwiched by a pair of sealing members 250A and 250B.

[0042] One of the first catalyst layer 120A and the second catalyst layer 120B is an anode catalyst layer, and the other is a cathode catalyst layer. Here, the first catalyst layer 120A is used as a cathode catalyst layer, and the second catalyst layer 120B is used as an anode catalyst layer. In this case, the first gas diffusion layer 130A corresponds to the cathode side gas diffusion layer, and the second gas diffusion layer 130B corresponds to the anode side gas diffusion layer.

[0043] Figure 2 Yes Figure 1 The diagram schematically shows the inside of the first catalyst layer 120A and the first gas diffusion layer 130A, which constitute a part of the membrane electrode assembly 100, in an enlarged manner. The first catalyst layer 120A includes a first particle-shaped conductive member 121 and a first fiber-shaped conductive member 122 as conductive materials. The first particle-shaped conductive member 121 carries catalyst particles. The first gas diffusion layer 130A includes a second particle-shaped conductive member 131 and a second fiber-shaped conductive member 132 as conductive materials. The mass-based content K2 of the second fiber-shaped conductive member 132 in the first gas diffusion layer 130A in the total of the second particle-shaped conductive member 131 and the second fiber-shaped conductive member 132 is greater than the mass-based content K1 of the first fiber-shaped conductive member in the first catalyst layer 120A in the total of the first particle-shaped conductive member 121 and the first fiber-shaped conductive member 122.

[0044] (Gas Diffusion Layer)

[0045] The first gas diffusion layer 130A (cathode side gas diffusion layer) and the second gas diffusion layer 130B (anode side gas diffusion layer) may be a structure having a substrate layer or a structure without a substrate layer. A structure without a substrate layer is more preferred. As a structure without a substrate layer, a microporous sheet formed of a conductive material and a polymer resin can be used. As a structure having a substrate layer, for example, a structure having a substrate layer and a microporous layer arranged on the catalyst layer side can be cited. The substrate layer can use a conductive porous sheet such as carbon cloth, carbon paper, etc. The microporous layer can use a mixture of a hydrophobic resin such as a fluororesin, a conductive carbon material, and a proton conductive resin (polymer electrolyte).

[0046] The substrate-free gas diffusion layer includes, for example, a conductive material (a second conductive material) and a polymer resin. As the polymer resin, a hydrophobic fluororesin described later may be used. The polymer resin is preferably 10 to 40 parts by mass relative to a total of 100 parts by mass of the conductive material and the polymer resin. The conductive material includes a fibrous conductive member (a second fibrous conductive member). The conductive material may also include a particle-shaped conductive member (a second particle-shaped conductive member).

[0047] As the particle-shaped conductive member and the fibrous conductive member, the materials described below can be used in the catalyst layer. From the viewpoint of improving the discharge efficiency of water, the fibrous conductive member (second fibrous conductive member) used in the gas diffusion layer can be the same type of material as the fibrous conductive member (first fibrous conductive member) used in the catalyst layer in contact with the gas diffusion layer. By making the physical properties of the fibrous conductive members contained in the catalyst layer and the gas diffusion layer in contact with each other similar, the discharge efficiency of water is improved.

[0048] The conductive material may include a particle-shaped conductive component and a fibrous conductive component, and may also include a plate-shaped material. The plate-shaped material may be arranged in the gas diffusion layer in a manner oriented along the surface direction (direction perpendicular to the thickness direction) of the gas diffusion layer. The plate-shaped material plays a role in improving the gas diffusion property in the surface direction of the gas diffusion layer. The plate-shaped material is particle-shaped when observed macroscopically, but is composed of plate-shaped particles when observed microscopically. Specific examples of plate-shaped materials include flaky graphite, graphitized polyimide film crushed material, graphene, etc. Among them, graphitized polyimide film crushed material and graphene are easily oriented in the surface direction of the gas diffusion layer, which is conducive to forming a thinner gas diffusion layer, and is suitable for improving the gas diffusion property in the surface direction of the gas diffusion layer.

[0049] In the first gas diffusion layer 130A and / or the second gas diffusion layer 130B, the content of the fibrous conductive member (second fibrous conductive member) in the conductive material (second conductive material) can be set to satisfy the above-mentioned condition 1 in relation to the conductive material (first conductive material) contained in the catalyst layer in contact with the gas diffusion layer. It is sufficient that at least one of the combination of the first gas diffusion layer 130A (cathode-side gas diffusion layer) and the first catalyst layer 120A (cathode catalyst layer) and the combination of the second gas diffusion layer 130B (anode-side gas diffusion layer) and the second catalyst layer 120B (anode catalyst layer) satisfies the above-mentioned condition 1. Figure 2 In the example, the combination of the first gas diffusion layer 130A and the first catalyst layer 120A satisfies the above condition 1. From the viewpoint of facilitating the discharge of water generated by power generation, suppressing the clogging of the gas diffusion path by the generated water, and improving the diffusibility of the reaction gas to the catalyst layer, at least the combination of the first gas diffusion layer 130A (cathode side gas diffusion layer) and the first catalyst layer 120A (cathode catalyst layer) satisfies the above condition 1.

[0050] The polymer resin has the function as a binder for bonding conductive materials to each other. From the viewpoint of suppressing water from being retained in the pores in the gas diffusion layer, it is preferably a hydrophobic fluororesin of more than 50 mass % of the polymer resin, and more preferably more than 90 mass % of the polymer resin. As fluororesin, PTFE (polytetrafluoroethylene), FEP (tetrafluoroethylene-hexafluoropropylene copolymer), PVdF (polyvinylidene fluoride), ETFE (tetrafluoroethylene-ethylene copolymer), PCTFE (polychlorotrifluoroethylene), PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer) etc. can be cited. Wherein, from the viewpoint of heat resistance, hydrophobicity, chemical resistance, fluororesin is preferably PTFE.

[0051] The gas diffusion layer is produced, for example, as follows.

[0052] First, a mixture containing a conductive material, a polymer resin, a surfactant and a dispersion medium is prepared. A mixing device may be a kneader or a mixer. In this case, it is preferred that a conductive material, a surfactant and a dispersion medium are added to the mixing device so that the conductive material is uniformly dispersed in the dispersion medium, and then the polymer resin is added to further disperse the conductive material. It is preferred that a moderate shear force is applied to the polymer resin so that the polymer resin is fibrillated. Examples of the dispersion medium include water, alcohols and glycols. Examples of the surfactant include polyoxyethylene alkyl ethers and alkylamine oxides.

[0053] Next, the obtained mixture is formed into a sheet by a forming method such as extrusion. The obtained sheet may be further rolled. A roll press may be used for rolling. The rolling conditions are not particularly limited, and by rolling at a linear pressure of 0.001 ton / cm to 4 ton / cm, a gas diffusion layer with high strength can be easily obtained.

[0054] Next, the sheet is fired to prepare a fired sheet from which the surfactant and the dispersion medium have been removed. The firing temperature can be any temperature at which the polymer resin does not deteriorate and the surfactant and the dispersion medium decompose or volatilize. When PTFE is used as the polymer resin, the firing temperature is preferably 310 to 340° C. The firing atmosphere can be an inactive atmosphere, such as an atmosphere such as nitrogen, argon, or a reduced pressure atmosphere. As long as most of the surfactant and the dispersion medium are removed from the sheet, it is not necessary to remove them completely.

[0055] (Catalyst layer)

[0056] The first catalyst layer 120A (cathode catalyst layer) includes, for example, a conductive material (first conductive material), catalyst particles, and a proton conductive resin. The catalyst particles are supported on the conductive material. The conductive material includes a particle-shaped conductive member (first particle-shaped conductive member). The conductive material may further include a fibrous conductive member (first fibrous conductive member). By including the fibrous conductive member, the gas diffusibility of the catalyst layer can be improved.

[0057] The second catalyst layer 120B (anode catalyst layer) may include a conductive material, catalyst particles supported on the conductive material, and a proton conductive resin, similarly to the first catalyst layer 120A (cathode catalyst layer). The conductive material may include a particle-shaped conductive member or a fibrous conductive member.

[0058] When the conductive material includes both a particulate conductive member and a fibrous conductive member, the catalyst particles may be carried on the particulate conductive member. The less the amount of catalyst particles carried on the fibrous conductive member, the higher the hydrophobicity of the fibrous conductive member. Therefore, drainage is easily improved and gas diffusion is easily improved. From the viewpoint of improving drainage, the catalyst particles may not be substantially carried on the fibrous conductive member. In other words, the catalyst particles may also be carried only on the particulate conductive member. Here, the catalyst particles are substantially not carried on the fibrous conductive member, which means that the ratio of the catalyst particles carried on the fibrous conductive member is less than 0.5 parts by mass relative to the total of 100 parts by mass of the catalyst particles carried on the fibrous conductive member and the fibrous conductive member.

[0059] In the first catalyst layer 120A and / or the second catalyst layer 120B, the content of the fibrous conductive component (first fibrous conductive component) in the conductive material (first conductive material) can be set in a manner that satisfies the above-mentioned condition 1 in terms of the relationship with the conductive material (second conductive material) contained in the gas diffusion layer in contact with the same catalyst layer.

[0060] Although the anode catalyst layer is not exposed to a highly oxidizing environment like the cathode catalyst layer, it is easy to become a lower humidity environment than the cathode catalyst layer because water is not generated by the reaction. As a result, the proton conductivity is easy to decrease. The composition and content ratio of the particle-shaped conductive member, the fibrous conductive member and the proton conductive resin can be changed to obtain a higher proton conductivity than the cathode catalyst layer.

[0061] (Fiber-shaped conductive member)

[0062] Examples of the fibrous conductive member include fibrous carbon materials such as vapor grown carbon fiber (VGCF (registered trademark)), carbon nanotubes, and carbon nanofibers. F , is not particularly limited, but is preferably 200 nm or less, more preferably 5 nm or more and 200 nm or less, and further preferably 10 nm or more and 170 nm or less. In this case, the volume ratio of the fibrous conductive member in the catalyst layer can be reduced, and the gas path can be fully ensured, thereby improving gas diffusivity. The diameter D of the fibrous conductive member is F The diameter is obtained by randomly taking out 10 fibrous conductive members from the catalyst layer and averaging the diameters thereof. The diameter is the length in a direction perpendicular to the longitudinal direction of the fibrous conductive member.

[0063] Regarding the length L of the fibrous conductive member (fiber length) F , is not particularly limited, and is preferably 0.2 μm or more and 20 μm or less, and more preferably 0.2 μm or more and 10 μm or less. In this case, at least a portion of the fibrous conductive member is oriented along the thickness direction of the catalyst layer, making it easy to ensure the gas diffusion path. The length L of the fibrous conductive member F The average fiber length is obtained by taking out 10 fibrous conductive members at random from the catalyst layer and averaging the fiber lengths of these fibrous conductive members. In addition, in the case of a substantially linear fibrous conductive member, the fiber length of the fibrous conductive member refers to the length of the straight line when connecting one end and the other end of the fibrous conductive member with a straight line.

[0064] The fibrous conductive member may have a hollow space (hollow portion) inside. At this time, in the catalyst layer, the two ends of the length direction of the fibrous conductive member may be opened respectively. The two ends of the length direction of the fibrous conductive member are opened respectively, which means that the hollow portion is connected to the outside through the opening. That is, the openings at the two ends of the fibrous conductive member are not blocked by any one of the electrolyte membrane and the gas diffusion layer, and the gas can enter and exit from the two ends.

[0065] A through hole connecting the hollow part and the outside can be provided on the side wall of the fibrous conductive member having a hollow part. The catalyst particles can be arranged on the side wall of the fibrous conductive member and fixed in a manner that blocks at least a portion of the through hole. The catalyst particles carried on the side wall in a manner that blocks at least a portion of the through hole can more effectively contact the reaction gas, greatly improving the reaction efficiency of the catalyst layer.

[0066] (Particle-shaped conductive member)

[0067] As the particle-shaped conductive member, there is no particular limitation, and for example, carbon black, spherical graphite, activated carbon, etc. can be cited. Among them, carbon black is preferred from the perspective of high conductivity and large pore volume. As carbon black, acetylene black, Ketjen black, thermal black, furnace black, channel black, etc. can be cited. Its particle size (or the length of the structure composed of a plurality of linked primary particles) is not particularly limited, and the particle size of the catalyst layer used in the past for fuel cells can be used.

[0068] (Catalyst particles)

[0069] The catalyst particles are not particularly limited, and examples thereof include catalyst metals such as Sc, Y, Ti, Zr, V, Nb, Fe, Co, Ni, Ru, Rh, Pd, Pt, Os, Ir, alloys selected from lanthanide elements and actinide elements, and simple substances. For example, catalyst particles used in the anode include Pt and Pt-Ru alloys. Catalyst particles used in the cathode include Pt and Pt-Co alloys. At least a portion of the catalyst particles is carried on a particle-shaped conductive member. The catalyst particles can be carried on a specific conductive member that ensures contact with the gas. This is because the catalyst particles are easy to contact with the gas, and the efficiency of the oxidation reaction or reduction reaction of the gas is improved.

[0070] From the viewpoint of immobilization of the catalyst particles, the diameter X of the catalyst particles is preferably 1 nm or more and 10 nm or less, more preferably 2 nm or more and 5 nm or less. When X is 1 nm or more, the catalytic effect brought by the catalyst particles can be fully obtained. When X is 10 nm or less, it is easy to make the catalyst particles supported on the side wall of the fibrous conductive member.

[0071] The diameter X of the catalyst particles is determined as follows.

[0072] For any catalyst particle observed in the TEM image of the catalyst layer, calculate the particle size when the particle is regarded as a sphere. Perform this operation on 100 to 300 catalyst particles observed in the TEM image and calculate the particle size of each. The average value of these particle sizes is taken as the diameter X of the catalyst particle.

[0073] (Proton conductive resin)

[0074] The proton conductive resin is not particularly limited, and examples thereof include perfluorocarbon sulfonic acid polymers, hydrocarbon polymers, etc. Among them, perfluorocarbon sulfonic acid polymers, etc. are preferred from the perspective of excellent heat resistance and chemical stability. As a perfluorocarbon sulfonic acid polymer, for example, Nafion (registered trademark) can be cited. The proton conductive resin coats at least a portion of the particle-shaped conductive member, the fibrous conductive member, and / or the catalyst particles.

[0075] The proton conductive resin is preferably contained in an amount of 25 to 65 parts by mass based on 100 parts by mass of the total of the conductive material and the proton conductive resin.

[0076] From the perspective of miniaturization of the fuel cell and maintaining low proton resistance to obtain high output power, the thickness of the catalyst layer is preferably as thin as possible. On the other hand, from the perspective of strength, it is preferably not too thin. Generally, if the proportion of the fibrous conductive member increases, the thickness of the catalyst layer tends to become thicker.

[0077] The thickness of the cathode catalyst layer is T C For example, the thickness T of the anode catalyst layer is 4 μm or more and 15 μm or less. A For example, the thickness T of the catalyst layer is 2 μm or more and 12 μm or less. C and T A The average thickness is obtained by averaging the distances when a straight line is drawn from one main surface to the other main surface along the thickness direction of the catalyst layer at any 10 locations in the cross section of the catalyst layer.

[0078] Regarding the proportion of the fibrous conductive member in the catalyst layer, the anode catalyst layer and the cathode catalyst layer both contain more than 20% of the fibrous conductive member relative to the particulate conductive member on a mass basis, thereby improving gas diffusivity. On the other hand, if the amount of the fibrous conductive member is increased, the film thickness of the catalyst layer tends to become thicker and the proton transfer resistance tends to increase. In addition, the catalyst layer is prone to cracking. From the viewpoint of suppressing the increase in the proton transfer resistance and suppressing cracks, the amount of the fibrous conductive member in the cathode catalyst layer and / or the anode catalyst layer can be less than 50% on a mass basis relative to the particulate conductive member.

[0079] The catalyst layer is produced, for example, as follows.

[0080] First, the catalyst particles and the particulate conductive member are mixed in a dispersion medium (e.g., water, ethanol, propanol, etc.). Next, while stirring the obtained dispersion, a proton conductive resin and a fibrous carbon material are added in sequence to obtain a catalyst dispersion. The proton conductive resin can be added in two or more times. In this case, the second and subsequent additions of the proton conductive resin can be performed together with the fibrous carbon material. Then, the obtained catalyst dispersion is applied to the surface of an electrolyte membrane or an appropriate transfer substrate sheet with a uniform thickness and dried to obtain a catalyst layer.

[0081] As the coating method, conventional coating methods can be cited, such as spraying, screen printing, and coating methods using various coating machines such as a blade coater, a knife coater, and a gravure coater. As a transfer substrate sheet, for example, a sheet with a smooth surface such as polyethylene terephthalate (PET), polypropylene, etc. is preferably used. When using a transfer substrate sheet, the resulting catalyst layer is transferred to an electrolyte membrane or a gas diffusion layer described later.

[0082] The transfer of the catalyst layer to the electrolyte membrane or gas diffusion layer is performed by bringing the surface of the catalyst layer opposite to the transfer substrate sheet into contact with the electrolyte membrane or gas diffusion layer. By bringing the smooth surface of the catalyst layer into contact with the electrolyte membrane or gas diffusion layer, the interface resistance with the catalyst layer is reduced, and the performance of the fuel cell is improved. The catalyst dispersion can also be directly applied to the electrolyte layer.

[0083] (Electrolyte membrane)

[0084] A polymer electrolyte membrane is preferably used as the electrolyte membrane 110. As a material of the polymer electrolyte membrane, the polymer electrolytes exemplified as the proton conductive resin can be mentioned. The thickness of the electrolyte membrane is, for example, 5 to 30 μm.

[0085] (Spacer)

[0086] The first spacer 240A and the second spacer 240B can be made of any material as long as they have airtightness, electronic conductivity and electrochemical stability. As such a material, a carbon material, a metal material, etc. are preferred. Carbon can be coated on a metal material. For example, the first spacer 240A and the second spacer 240B are obtained by punching a metal plate into a specified shape and performing a surface treatment.

[0087] In this embodiment, a gas flow path 260A is formed on the surface of the first separator 240A that contacts the first gas diffusion layer 130A. On the other hand, a gas flow path 260B is formed on the surface of the second separator 240B that contacts the second gas diffusion layer 130B. The shape of the gas flow path is not particularly limited, and may be formed in a straight line, a serpentine shape, or the like.

[0088] (Sealing member)

[0089] The sealing members 250A and 250B are made of elastic materials to prevent the fuel and / or oxidant from leaking from the gas flow paths 260A and 260B. The sealing members 250A and 250B have, for example, a frame-like shape that annularly surrounds the peripheral edge of the first catalyst layer 120A and the second catalyst layer 120B. As the sealing members 250A and 250B, known materials and known structures can be respectively adopted.

[0090] Hereinafter, the present invention will be described in more detail based on examples. However, the present invention is not limited to the following examples.

[0091] [Example]

[0092] (1) Preparation of dispersion for cathode catalyst layer

[0093] A particle-shaped conductive member (carbon black) carrying catalyst particles (Pt-Co alloy) is added to an appropriate amount of water and stirred to disperse. After adding an appropriate amount of ethanol while stirring the obtained dispersion, 35 parts by mass of a fibrous conductive member (first fibrous conductive member) (vapor-grown carbon fiber, average diameter 150 nm, average fiber length 10 μm) and 100 parts by mass of a proton conductive resin (perfluorocarbon sulfonic acid polymer) are added to 100 parts by mass of the above-mentioned particle-shaped conductive member carrying catalyst particles, and stirred to prepare a catalyst dispersion for a cathode catalyst layer.

[0094] (2) Preparation of dispersion for anode catalyst layer

[0095] A particulate conductive member (carbon black) carrying catalyst particles (Pt) is added to an appropriate amount of water and stirred to disperse. After adding an appropriate amount of ethanol while stirring the obtained dispersion, 35 parts by mass of a fibrous conductive member (vapor-grown carbon fiber, average diameter 150 nm, average fiber length 10 μm) and 120 parts by mass of a proton conductive resin (perfluorocarbon sulfonic acid polymer) are added to 100 parts by mass of the above-mentioned particulate conductive member carrying catalyst particles, and stirred to prepare a catalyst dispersion for an anode catalyst layer.

[0096] (3) Fabrication of gas diffusion layer

[0097] A particle-shaped conductive component (carbon black), a fibrous conductive component (vapor-grown carbon fiber, average diameter 150nm, average fiber length 10μm), a surfactant and a dispersion medium are placed in a stirring device, stirred and kneaded to uniformly disperse the materials. Then, PTFE is added as a polymer resin and uniformly dispersed to obtain a kneaded product. Next, the kneaded product is extruded, stretched into a sheet and dried. The obtained sheet is sintered at 310°C to remove the surfactant and dispersion medium to obtain a gas diffusion layer.

[0098] The contents of the particulate conductive material, the fibrous conductive material and the polymer resin in the gas diffusion layer were adjusted within the range of 5% to 35% by mass for the particulate conductive material, 35% to 80% by mass for the fibrous conductive material and 10% to 40% by mass for the polymer resin. Thus, four types of gas diffusion layers A1 to A3 and B1 with different mass-based contents K2 of the fibrous conductive member in the conductive material were prepared.

[0099] In the gas diffusion layers A1, A2, A3, and B1, the mass-based contents K2 of the fibrous conductive members in the conductive material were 0.88, 0.86, 0.71, and 0.26, respectively.

[0100] (4) Fabrication of single battery unit

[0101] Two PET sheets were prepared, and the obtained catalyst dispersion for the cathode catalyst layer was applied to the smooth surface of one PET sheet with a uniform thickness by screen printing, and the obtained catalyst dispersion for the anode catalyst layer was applied to the smooth surface of the other PET sheet with a uniform thickness. Then, the two catalyst layers were formed by drying. The film thickness of the cathode catalyst layer was 6 μm, and the film thickness of the anode catalyst layer was 4.5 μm.

[0102] The obtained catalyst layers were transferred to the two main surfaces of the electrolyte membrane with a thickness of 15 μm, and a cathode was formed on one surface of the electrolyte membrane and an anode was formed on the other surface. Then, two gas diffusion layers were prepared, one of the two layers was abutted against the anode, and the other was abutted against the cathode, to produce a membrane electrode assembly. In the membrane electrode assembly, the mass basis content K1 of the fibrous conductive members of the cathode catalyst layer and the anode catalyst layer in the conductive material was set to 0.26.

[0103] Next, a frame-shaped sealing member was arranged so as to surround the anode and cathode, and the whole was sandwiched by a pair of stainless steel flat plates (spacers) having gas flow paths at the portions in contact with the gas diffusion layers, thereby completing a test cell unit.

[0104] Thus, test cell X1 using gas diffusion layer A1, test cell X2 using gas diffusion layer A2, test cell X3 using gas diffusion layer A3, and test cell Y1 using gas diffusion layer B1 were manufactured and their performances were evaluated.

[0105] <Evaluation>

[0106] The single cell unit was heated to 80°C, a fuel gas with a relative humidity of 100% was supplied to the anode, and an oxidant gas (air) with a relative humidity of 100% was supplied to the cathode. The fuel gas and the oxidant gas were pressurized to a cell inlet gas pressure of 40 to 120 kPa at each current density and supplied. Then, the load control device was controlled so that the current flowed constantly, and the voltage (initial voltage) of the single cell unit was measured while changing the current density relative to the electrode area of ​​the anode and cathode.

[0107] For the single battery units X1 to X3 and Y1, the maximum output density W is evaluated respectively. max The evaluation results are shown in Table 1. In Table 1, the maximum output density W max , showing the maximum output density W in the single battery cell Y1 max The measured value is set as a relative value of 100. In the battery cells X1 to X3 in which the content K2 of the fibrous conductive member in the conductive material of the gas diffusion layer is set to be greater than the content K1 of the fibrous conductive member in the conductive material of the catalyst layer, the maximum output density is improved compared with the battery cell Y1 in which K2 is set to be the same as K1.

[0108] [Table 1]

[0109]

[0110] Industrial Applicability

[0111] The fuel cell of the present invention can be suitably used as a power source for a stationary household cogeneration system or a vehicle power source. The present invention is suitably applied to a polymer electrolyte fuel cell, but is not limited thereto and can be applied to fuel cells in general.

[0112] The present invention has been described with respect to the present preferred embodiments, but such disclosure should not be interpreted in a limiting manner. By reading the above disclosure, various deformations and changes are undoubtedly obvious to those skilled in the art in the technical field to which the present invention belongs. Therefore, the attached technical scheme should be interpreted as including all deformations and changes without departing from the true purpose and scope of the present invention.

[0113] Description of Reference Numerals

[0114] 100: membrane electrode assembly, 110: electrolyte membrane, 120A: first catalyst layer, 120B: second catalyst layer, 130A: first gas diffusion layer, 130B: second gas diffusion layer, 200: fuel cell (single cell unit), 240A: first separator, 240B: second separator, 250A, 250B: sealing member, 260A, 260B: gas flow path

Claims

1. A membrane electrode assembly for a fuel cell, comprising: Electrolyte membrane; a pair of catalyst layers, the pair of catalyst layers being stacked on one surface and the other surface of the electrolyte membrane, respectively; and a pair of gas diffusion layers, the pair of gas diffusion layers being stacked on a surface of one catalyst layer of the pair of catalyst layers opposite to the electrolyte membrane and a surface of the other catalyst layer of the pair of catalyst layers opposite to the electrolyte membrane, respectively; One catalyst layer of the pair of catalyst layers includes catalyst particles A and a first conductive material, Among the pair of gas diffusion layers, the gas diffusion layer in contact with the one catalyst layer includes a second conductive material, The first conductive material includes a first particle-shaped conductive member and a first fibrous conductive member. The second conductive material includes at least the second fibrous conductive member of a second particulate conductive member and a second fibrous conductive member, The first fibrous conductive member and the second fibrous conductive member are linear, and the length thereof is 0.2 μm or more and 20 μm or less, A content K2 of the second fibrous conductive member in the second conductive material based on mass is greater than a content K1 of the first fibrous conductive member in the first conductive material based on mass.

2. The membrane electrode assembly according to claim 1, wherein: A ratio of a fiber length of the second fibrous conductive member to a fiber length of the first fibrous conductive member is in a range of 0.5 to 2.

0.

3. The membrane electrode assembly according to claim 1, wherein: A ratio of a fiber diameter of the second fibrous conductive member to a fiber diameter of the first fibrous conductive member is in a range of 0.5 to 2.

0.

4. The membrane electrode assembly according to any one of claims 1 to 3, wherein The first fibrous conductive member and the second fibrous conductive member include the same material.

5. The membrane electrode assembly according to any one of claims 1 to 3, wherein The content K2 of the second fibrous conductive member in the second conductive material is 60 mass % or more.

6. The membrane electrode assembly according to any one of claims 1 to 3, wherein The one catalyst layer constitutes a cathode of the fuel cell.

7. The membrane electrode assembly according to claim 6, wherein: The other catalyst layer of the pair of catalyst layers comprises catalyst particles B and a third conductive material, The third conductive material includes a third particulate conductive member and a third fibrous conductive member.

8. The membrane electrode assembly according to claim 7, wherein: A ratio K3 / K1 of a mass-based content K3 of the third fibrous conductive member to the content K1 in the third conductive material is in the range of 0.5 ≤ K3 / K1 ≤ 2.

0.

9. The membrane electrode assembly according to claim 7, wherein: The content K2 is greater than a content K3 of the third fibrous conductive member in the third conductive material based on mass.

10. The membrane electrode assembly according to claim 7, wherein: the gas diffusion layer in contact with the other catalyst layer comprises a fourth conductive material, The fourth conductive material includes at least the fourth fibrous conductive member of a fourth granular conductive member and a fourth fibrous conductive member. A content K4 of the fourth fibrous conductive member in the fourth conductive material based on mass is greater than a content K3 of the third fibrous conductive member in the third conductive material based on mass.

11. The membrane electrode assembly according to claim 7, wherein: the gas diffusion layer in contact with the other catalyst layer comprises a fourth conductive material, The fourth conductive material does not include the fourth fibrous conductive member, or the mass-based content K4 of the fourth fibrous conductive member in the fourth conductive material is smaller than the content K2. 12 . A fuel cell comprising the membrane electrode assembly according to claim 1 .

Citation Information

Patent Citations

  • Gas diffusion layer for fuel cell, its manufacturing method, and fuel cell using it

    JP2007141783A

  • MEA for fuel cell and fuel cell

    JP2006085929A